MEMPERKUAT KINERJA KARYAWAN DENGAN MEREDUKSI FAKTOR STRES DAN MEMBANGUN LINGKUNGAN KERJA YANG NYAMAN - Veritia Veritia (Universitas Pamulang, 2022)
This study aims to determine and analyze the effect of work stress and physical work environment on employee performance at PT. Jet Technology Express (J&T Express) Ciledug Tangerang Drop Center Branch, either partially or simultaneously. The method used is descriptive quantitative. The sampling technique used saturated sampling where the entire population was used as a sample, in this study there were 55 respondents. Data analysis used validity test, reliability test, classic assumption test, regression analysis, coefficient of determination analysis, and hypothesis testing. The results showed that there was a positive influence between work stress and employee performance partially. Where is the simple linear regression equation Y = 16.243 + 0.678 X1 means that it has a positive effect, the reliability test r = 0.948 is included in the strong category, the coefficient of determination is 48.9% and the remaining 51.1% is influenced by other factors, the t test is tcount 7.115 > ttable 2.00665 then Ha is accepted and Ho is rejected. The results showed that there was a positive influence between the physical work environment and employee performance partially. Where is the simple linear regression equation Y = 31.298 + 0.328 X2 means that it has a positive effect, the reliability test r = 0.881 is included in the strong category, the coefficient of determination is 20.6% and the remaining 80.4% is influenced by other factors, the t test is tcount 3.706 > ttable 2.00665 then Ha is accepted and Ho is rejected. The results showed that there was a positive influence between the variables of work stress and the physical work environment on employee performance simultaneously, where the multiple regression equation Y = 15.932 + 0.805X1 +0.125X2 means a positive effect, the reliability test r = 0.956 is included in the strong category, the coefficient of determination of 50.1% and the remaining 49.9% which is influenced by other factors, the f test of fcount 26.134 > ftable 3.172 means that it can be concluded that the variables of work stress and physical work environment have a significant effect on employee performance.Keywords: Work Stress, Physical Work Environment, Employee Performance